Digital Transformation of Madrasahs: The Strategic Role of EMIS-Based SIMDIK in Improving Institutional Performance - Setiawan, Usep; Bagus, Solihah; Wulandari, Dyah; Megawati, Irma; Salman, Salman (Pascasarjana Universitas KH. Abdul Chalim, 2025)
This study analyzes the implementation of the EMIS-based SIMDIK program at Madrasah Aliyah Purwakarta, which faces challenges such as limited budgets, human resources, infrastructure, and internet network issues in remote areas. The study aims to evaluate the implementation of SIMDIK in improving the performance of madrasahs, covering planning, organization, implementation, supervision, identification of problems, solutions, and performance outcomes. The qualitative research method, with observations, interviews, and documentation, is based on G.R. Terry’s POAC theory and Edison’s performance theory. The findings show: (1) planning is by the Ministry of Religion regulations; (2) organization involves the designation of a SIMDIK operator, though limited to one person and assisted by other non-permanent personnel; (3) implementation is directed; (4) supervision involves the head of the madrasah, committee, and foundation; (5) main challenges include human resources, infrastructure, funding, and stakeholder support; (6) proposed solutions are a special budget request and honorarium for managers; (7) the use of EMIS-based SIMDIK has contributed to improving madrasah performance. Implications: This study recommends increasing the special budget and recognition systems for SIMDIK managers to improve program effectiveness. Greater stakeholder support is also expected to accelerate progress in madrasah infrastructure and human resource capacity.